2020
DOI: 10.3390/cancers12082272
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Gut Microbial Biofilms—A Key to Hinder Colon Carcinogenesis?

Abstract: Colorectal cancer (CRC) is a global public health issue which poses a substantial humanistic and economic burden on patients, healthcare systems and society. In recent years, intestinal dysbiosis has been suggested to be involved in the pathogenesis of CRC, with specific pathogens exhibiting oncogenic potentials such as Fusobacterium nucleatum, Escherichia coli and enterotoxigenic Bacteroides fragilis having been found to contribute to CRC development. More recently, it has been shown that initiation of CRC de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 161 publications
(221 reference statements)
0
33
0
12
Order By: Relevance
“…Within the microbial communities in the gut, indole production affects spore formation, plasmid stability, biofilm formation, antibiotic tolerance, cell division, and virulence [ 13 ]. Within the host, indoles activate signaling pathways that result in changes in intestinal epithelial barrier function, reduce permeability, promote immune tolerance, evict pathogens, reduce inflammation, and, control mucin production [ 12 , 85 , 90 , 91 , 92 , 93 , 94 , 95 ]. Colonization of germ-free mice for 4 weeks with C. sporogenes or a mutant (fldC) lacking the an enzyme necessary for indole (indole-3-propionic acid (IPA)) production, resulted in serum concentrations of 80 μM in mice colonized with wild-type but undetectable levels in mice colonized with the mutant strain.…”
Section: Contribution Of the Microbiota In Trp Metabolismmentioning
confidence: 99%
“…Within the microbial communities in the gut, indole production affects spore formation, plasmid stability, biofilm formation, antibiotic tolerance, cell division, and virulence [ 13 ]. Within the host, indoles activate signaling pathways that result in changes in intestinal epithelial barrier function, reduce permeability, promote immune tolerance, evict pathogens, reduce inflammation, and, control mucin production [ 12 , 85 , 90 , 91 , 92 , 93 , 94 , 95 ]. Colonization of germ-free mice for 4 weeks with C. sporogenes or a mutant (fldC) lacking the an enzyme necessary for indole (indole-3-propionic acid (IPA)) production, resulted in serum concentrations of 80 μM in mice colonized with wild-type but undetectable levels in mice colonized with the mutant strain.…”
Section: Contribution Of the Microbiota In Trp Metabolismmentioning
confidence: 99%
“…Dysregulation of the vaginal environment is a risk factor for many diseases, as upward colonization of the reproductive tract with microbiota, especially anaerobic bacteria, serves as a primary driver for inflammation, and may be involved in the development of diseases, such as gynecological cancers (37)(38)(39). Where there is persistent dysbiosis of the microbial environment, altered immune and metabolic signaling can result in oxidative stress and the recruitment of immune cells which release reactive oxygen species (ROS), which may result in inflammationdriven carcinogenesis (40,41). At present, the study of endometrial microbiota has reported that EC is associated with particular microorganisms (42).…”
Section: Microbial Communities In Female Reproductive Tractmentioning
confidence: 99%
“…when the Greek physician Hippocrates said, “death is in the bowels” and also “poor digestion is the origin of all evil” ( Iebba et al, 2016 ). Over the years, researchers have discovered that there are strong correlations between the gut microbiome and important systems in the human body, such as the brain in the nervous system and the immune system that protects the body against deadly infections and cancer ( Schwabe and Jobin, 2013 ; Gonzalez-Perez and Lamousé-Smith, 2017 ; Yang and Jobin, 2017 ; Chew et al, 2020 ; Johnson et al, 2020 ; Lee et al, 2021 ). Existing evidence has demonstrated that gut dysbiosis can contribute to the etiology of numerous human diseases, including diabetes, atherosclerosis, inflammatory bowel disease, atopic dermatitis, autism, or even the development of cancer ( Adlerberth et al, 2007 ; Michail et al, 2012 ; Morgan et al, 2012 ; Mulle et al, 2013 ; Vinje et al, 2014 ; Zackular et al, 2014 ; Song et al, 2016 ; Gózd-Barszczewska et al, 2017 ; Jie et al, 2017 ; Ni et al, 2017 ; Lee et al, 2020a , b ; Selvaraj et al, 2020 ; Wang et al, 2021 ).…”
Section: Importance Of Gut Microbiome In Diseasesmentioning
confidence: 99%